Small scale broiler farming at Santhia upazilla of Pabna District of Bangladesh (Bangladesh Journal of Animal Science, 2013)
The experiment was conducted for profiling the existing broiler farming at Santhia upazilla under Pabna District during the period from February to March, 2012. Data were collected using an interview schedule from 50 randomly selected respondents who were involved in broiler farming. In this study out of 50 respondents 60% were engaged in  agriculture, 36% businessman  and  4%  were in services. About 48% respondents had small size farms (100-500 birds), 40% had medium (501-1000 birds) and remaining were large size (1001-2000 birds). Most of the respondents reared Cobb-500 strain, those were purchased from Kazi Farms Ltd. Out of 50 respondents 30% took necessary suggestions from the experienced farmers, 90% farmers regularly vaccinated their broilers and 70% farmers taken short training on broiler farming. About 78% respondents considered market weight as 1.5 kg per bird, whereas the rest 22% sold broiler weighing about 1.8 kg per bird. Most of the respondents (64%) sold broiler at 30-33 d of age and about 80% respondents marketing their broiler at 110-115 taka per kg live bird. About 36% respondents had production cost approximately 90-95 taka per kg bird. In this study, about 36% respondents reported more marketing age of birds, 32% reported higher cost of production and 30% reported lack of training facilities. In conclusion, the result of present  study could  be considered useful to farmers and researchers to identify the overall problems and their remedies on management and marketing related to broiler production.DOI: http://dx.doi.org/10.3329/bjas.v41i2.14129Bang. J. Anim. Sci. 2012. 41 (2): 116-119